Preliminary Phytochemical and Pharmacological Investigations of Alpinia conchigera Griff. and Plumbago indica L. - Ibrahim, Mohammed; Baura, Joy; Islam, Torequl; Homa, Zilly; Chowdhury, M Mohi Uddin; Hossain, Md Aslam; Rashid, Mohammad A (Bangladesh Pharmaceutical Journal, 2012)
Preliminary phytochemical screenings with the crude extractives of Alpinia conchigera Griff. and Plumbago indica L. demonstrated the presence of alkaloids, steroids, saponins and reducing sugars. The antibacterial and antifungal activities of methanol extracts of A. conchigera and P. indica have been evaluated against 4 Gram positive and 7 Gram negative pathogenic bacteria and 7 fungi using ciprofloxacin and fluconazole as standards, respectively, where the extract showed varying degrees of antimicrobial activity with zone of inhibition ranging from 15.0 to 27.0 mm. A. conchigera demonstrated significant zone of inhibition against Aspergillus niger, Blastomyces dermatitidis, Staphylococcus aureus, Salmonella typhi, Shigella dysenteriae, Bacillus cereus Pseudomonas aeruginosa, Shigella sonnei, Vibrio cholerae while P. indica revealed strong inhibitory activity against Candida albicans, Blastomyces dermatitidis, Bacillus cereus, Staphylococcus aureus, Escherichia coli and Salmonella paratyphi. The MICs of the both plant extractives were found to be 31.25 ?g/ml against B. cereus, S. paratyphi, V. cholerae, A. niger and B. dermatitidis. In the brine shrimp lethality bioassay, the LC50 and LC90 of A. conchigera and P. indica were found to be 6.1 & 12.2 ?g/ml and 5.0 &12.0 ?g/ml, respectively. A significant dose dependent antidiarrhoeal, antimotility and analgesic activities were observed during screening in mice. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12581 Bangladesh Pharmaceutical Journal 15(2): 153-157, 2012